Waveform-regulated catalyst-free NOx removal in micro-hollow surface dielectric barrier discharge - Mengwei Sun; Dingkun Yuan; Zhongqian Ling; Fawei Lin; Guangxue Zhang; Shahong Zhu (Journal of Environmental Chemical Engineering, 2026)

Flash-Joule carbon-based hierarchical evaporator for water recovery and synergistic heavy-metal sequestration from E-waste leachates - Chenxu Zhong; Chujun Luan; Jianlin Yu; Lei Che; Guanyi Chen; Fawei Lin (Chemical Engineering Journal, 2026)

A critical review comparing catalytic ozone decomposition with catalytic ozonation of VOCs - Luyang Zhang; Ziyu Tang; Yongtao Li; Fawei Lin (ENGINEERING Environment, 2026)

Microwave co-pyrolysis of oily sludge and corn stalk under different microwave absorbents - Jiantao Li; Zhenlin Xie; Shupeng Zhang; Zizhen Niu; Zhihua Liu; Rui Zhang; Fawei Lin; Guanyi Chen (Journal of Hazardous Materials, 2026)

Catalyst-free aqueous-phase oxidation of toluene by ozone micro-nanobubbles coupled with H2O2 via interfacial reactive oxygen species - Tianzhi Wang; Hangjia Zhao; Yongtao Li; Ziyue Jiang; Lingye Zhang; Andrei Ivanets; Fawei Lin (Journal of Hazardous Materials, 2026)

Environmental risks and upcycling potential in ternary geopolymer development for oily sludge pyrolysis byproducts - Chenxu Zhong; Chujun Luan; Xuan Guo; Fawei Lin; Jingwei Li; Beibei Yan; Zhanjun Cheng; Eminov Ashraf Mamurovich; Bigaliev Aitkhazha Bigalievich; Guanyi Chen (Journal of Environmental Chemical Engineering, 2026)

Spatial patterns and environmental drivers of evapotranspiration across the Chinese Grassland Transect - Lexin Ma; Zhi Chen; Tianxiang Hao; Meng Yang; Quanhong Lin; Weikang Zhang; Lang Han; Zhaogang Liu; Mingyu Sun; Yong Lin; Xianjin Zhu; Shiping Chen; et al. (Journal of Hydrology, 2026)

Comparative study by microwave, fixed-bed and rotary kiln pyrolysis of oily sludge: Petroleum hydrocarbons, N-/S-/Cl-containing pollutants and heavy metals - Jiantao Li; Hongdi Yu; Fawei Lin; Shupeng Zhang; Zizhen Niu; Zhihua Liu; Rui Zhang; Guijian Liu; Xiaojiang Shen; Beibei Yan; Guanyi Chen (Journal of Environmental Chemical Engineering, 2026)

Balanced water transport and evaporation by directionally wettability-gradient assembled evaporator for cascaded anti-oil and desalination - Chujun Luan; Fawei Lin; Huiyi Mao; Xudong Wang; Ziyu Chen; Aitkhazha Bigalievich Bigaliev; Ashraf Mamurovich Eminov; Guanyi Chen (Water Research, 2026)

Mid-late Holocene environmental change and social resilience in Central Plains of China: Evidence from Sha-Ying Rivers floodplain - Wei Li; YiHsien Lin; Linjing Liu; Xiaochen Pei; Ligang Zhou; Yanpeng Cao; Chen Liu; Hui Wang; Peng Lu; Yijie Zhuang; Meilin Guo; Fawei Liang; et al. (Quaternary Science Reviews, 2026)

Controlling product selectivity and residual carbon behavior in biomass pyrolysis via pulse-structured joule heating - Yang Liu; Ruming Pan; Renaud Ansart; Chenxu Zhong; Yue Niu; Hongdi Yu; Fawei Lin; Gérald Debenest (Process Safety and Environmental Protection, 2025)

Solar-driven interfacial evaporation toward sustainable multimedia remediation via multifunctional platforms - Chenxu Zhong; Jianlin Yu; Chujun Luan; Xiaoqiang Cui; Fawei Lin; Guanyi Chen (Chemical Engineering Journal, 2025)

Geometrically optimized CuO/Cu foam evaporators enabling salt rejection and organic degradation for sustainable hypersaline wastewater remediation - Chujun Luan; Chenxu Zhong; Fawei Lin; Huiyi Mao; Hongyun Yao; Xiaoqiang Cui; Guanyi Chen (Chemical Engineering Journal, 2025)

Multiple defects construction of Co loading on Ni foam to activate water for promoting catalytic ozonation of dichloromethane - Yongtao Li; Chujun Luan; Fawei Lin; Xueyan Zhu; Beibei Yan; Zhanjun Cheng; Guanyi Chen; Chi He (Journal of Hazardous Materials, 2025)

Exploration on using solid waste-derived sulphoaluminate composite as low-cost binder for high-impermeability stabilization of sandy soil - Shuang Zhang; Jingwei Li; Wenbin Shi; Fawei Lin; Bigaliev Aitkhazha Bigalievich; Eminov Ashraf Mamurovich; Wenlong Wang (Waste Disposal & Sustainable Energy, 2025)

Ignition, combustion and pollutant emissions characteristics of excavated waste in low oxygen concentration and O2/CO2 atmosphere - Jingwen Lv; Beibei Yan; Shengquan Zhou; Zhaoting Wu; Xiaoyun Liu; Sensen Lu; Xiaochao Zhu; Yunan Sun; Jian Li; Fawei Lin; Guanyi Chen (Waste Management, 2025)

Promoting strategies for biological stability in drinking water distribution system from the perspective of micro-nano bubbles - Peiyuan Luo; Tianzhi Wang; Fawei Lin; Aibao Luo; Manuel Fiallos; Ahmed Khaled Abdella Ahmed; Soon-Thiam Khu (Science of The Total Environment, 2024)

Comparison of environmental impacts from pyrolysis, gasification, and combustion of oily sludge - Hongdi Yu; Fawei Lin; Xuan Guo; Chujun Luan; Jiantao Li; Rundong Li; Lei Che; Wangyang Tian; Guanyi Chen (Journal of Hazardous Materials, 2024)

Effective decontamination of DR-81 dye from aqueous solutions using eco-friendly graphene oxide nanoparticles - Eslam Salama; Ahmed E. Mansy; Zhen-Yu Tian; Safaa Mohamed; Ning Li; Fawei Lin; Mona Ossman (Environmental Science and Pollution Research, 2024)

Green transformation of oily sludge through geopolymer: Material properties and hydration mechanisms - Xuan Guo; Hongdi Yu; Hongyun Yao; Fawei Lin; Eslam Salama; Mona Ossman; Beibei Yan; Guanyi Chen (Chemosphere, 2024)

Intelligent technologies powering clean incineration of municipal solid waste: A system review - Junyu Tao; Zaixin Li; Chao Chen; Rui Liang; Shuang Wu; Fawei Lin; Zhanjun Cheng; Beibei Yan; Guanyi Chen (Science of The Total Environment, 2024)

Critical review for the potential analysis of material utilization from inorganic industrial solid waste - Xuan Guo; Menglan Zeng; Hongdi Yu; Fawei Lin; Jingwei Li; Wenlong Wang; Guanyi Chen (Journal of Cleaner Production, 2024)

Co-pyrolysis of saw dust and oily sludge with waste-heat utilization of steel slag on rotary kiln simulated engineering practice - Hongdi Yu; Fawei Lin; Xuan Guo; Hongyun Yao; Fa Zheng; Jiantao Li; Meng Zhang; Rundong Li; Beibei Yan; Guanyi Chen (Fuel, 2024)

Comparative study by microwave pyrolysis and conventional pyrolysis of pharmaceutical sludge: Resourceful disposal and antibiotic adsorption - Yifan Zhou; Fawei Lin; Zhongqian Ling; Mingxiu Zhan; Guangxue Zhang; Dingkun Yuan (Journal of Hazardous Materials, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Precipitation consistently promotes, but temperature oppositely drives carbon fluxes in temperate and alpine grasslands in China - Zhaogang Liu; Zhi Chen; Meng Yang; Tianxiang Hao; Guirui Yu; Xianjin Zhu; Weikang Zhang; Lexin Ma; Xiaojun Dou; Yong Lin; Wenxing Luo; Lang Han; et al. (Agricultural and Forest Meteorology, 2024)

La0.7(Ca, Sr)0.3Ni0.6Mn0.5O3 perovskites for photothermal catalytic reforming of toluene: The role of oxygen species in the photothermal synergistic effect - Xiaoshan Dong; Jian Wang; Fawei Lin; Jian Li; Tianxiao Yu; Beibei Yan; Guanyi Chen (Fuel, 2023)

Pyrolysis/combustion potential and heavy metal risk of oily sludge and derived products in industrial scale - Hongdi Yu; Jiantao Li; Fawei Lin; Menglan Zeng; Rundong Li; Beibei Yan; Guanyi Chen (Fuel, 2023)

UV–vis-enhanced photothermal catalytic reforming of biomass model tar via LaMnxNi1-xO3 perovskite catalyst - Xiaoshan Dong; Xiaochao Zhu; Fawei Lin; Beibei Yan; Jian Li; Guanyi Chen (Chemical Engineering Journal, 2023)

Tentative exploration on water-promoted catalytic ozonation of Cl-VOCs and feasibility of application in complex flue gas over monolithic cobalt catalyst - Li Xiang; Luyang Zhang; Jiaming Shao; Fawei Lin; Zhihua Wang; Beibei Yan; Guanyi Chen (Journal of Hazardous Materials, 2023)

Comprehensive review on catalytic degradation of Cl-VOCs under the practical application conditions - Fawei Lin; Li Xiang; Zhiman Zhang; Na Li; BeiBei Yan; Chi He; Zhengping Hao; Guanyi Chen (Critical Reviews in Environmental Science and Technology, 2022)

Alpine grassland plants grow earlier and faster but biomass remains unchanged over 35 years of climate change - Hao Wang; Huiying Liu; Guangmin Cao; Zhiyuan Ma; Yikang Li; Fawei Zhang; Xia Zhao; Xinquan Zhao; Lin Jiang; Nathan J. Sanders; Aimée T. Classen; Jin‐Sheng He (Ecology Letters, 2020)
Satellite data indicate significant advancement in alpine spring phenology over decades of climate warming, but corresponding field evidence is scarce. It is also unknown whether this advancement results from an earlier shift of phenological events, or enhancement of plant growth under unchanged phenological pattern. By analyzing a 35‐year dataset of seasonal biomass dynamics of a Tibetan alpine grassland, we show that climate change promoted both earlier phenology and faster growth, without changing annual biomass production. Biomass production increased in spring due to a warming‐induced earlier onset of plant growth, but decreased in autumn due mainly to increased water stress. Plants grew faster but the fast‐growing period shortened during the mid‐growing season. These findings provide the first in situ evidence of long‐term changes in growth patterns in alpine grassland plant communities, and suggest that earlier phenology and faster growth will jointly contribute to plant growth in a warming climate.

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)